Estudo fitoquímico de Citrus: resistência a Xylella fastidiosa e interação com Oncometopia facialis - Abdelnur, Patrícia Verardi (2006)
This work describes sixteen substances isolated by C. limonia: xanthyletin, seselin, xanthoxyletin, trans-kellactone, trans-decursidinol, junosmarin, scopoletin, isoscopoletin, demethylsuberosin, xanthoarnol, clausarin, limonianin, 5,4 - dihydroxy-6-(3 -methyl-2 -buthenyl)-2 ,2 -dimethylpyrano(5 ,6 -7,8)flavanone, β- sitosterol, estigmasterol e campesterol. Three of them are especially important: 5,4 -dihydroxy-6-(3 -methyl-2 -buthenyl)-2 ,2 -dimethylpyrano(5 ,6 -7,8)flavanone that was unknown in the literacy, trans-kellactone and trans-decursidinol that weren t found previously in the Rutaceae family but at Apiaceae family. The chemical constituents isolated by the upper and low parts from the grafted plant (C. sinensis on C. limonia) and from ungrafted C. limonia were compared. It indicated that the grafted plant has a metabolic translocation process. The Minimum Inhibitory Concentration of many substances isolated from plants of Rutaceae family was related. The test was against the bacteria Xylella fastidiosa that causes Citrus Variegated Chlorosis. The successful classes the pyranocoumarins and flavones whose MIC was 1,0 mg/mL. We have studied the plant-insect interaction and discovered that the grafted plant (C. sinensis on C. limonia) undergoes chemical alteration of the volatile compounds and essential oils when it is in contact with the sharpshooter. The sharpshooters Oncometopia facialis belongs to the Cicadellidae family and carries the Xylella fastidiosa. This chemical alteration was greater in the volatile compounds than in the essential oils of the plants. Different amounts of Hesperidin were found in the grafted plant when different species of Citrus were analized: C. limonia without CVC, C. reticulata without CVC, C. sinensis on C. limonia with and without CVC. The C. limonia presented the lower amount of the secondary metabolic and the C. sinensis on C. limonia presents the higher amount. The higher amounts of Hesperidin were found in sick plants witch corresponds the metabolic alteration that occurs when the plant is infected by the bacteria.